2015
DOI: 10.1186/s12906-015-0551-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antitumor property of extracts and steroidal alkaloids from the cultivated Bulbus Fritillariae ussuriensis and preliminary investigation of its mechanism of action

Abstract: BackgroundCancer is well known as a leading cause of death in the world. At present, it is the very active area to search for anticancer drugs from natural products. In this study, we evaluated the antitumor property of chloroform extract (CE), n-hexane extract (HE), water extract (WE) and steroidal alkaloids from the cultivated Bulbus Fritillariae ussuriensis (BFU) and its preliminary mechanism for its action was investigated.MethodsFirstly, cytotoxicity of the different extracts from BFU against Lewis lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…Of course, some monomer chemical compositions have also been reported to exhibit advantageous effects on the treatment of endometrial cancer or ovarian cancer. A recent research suggested that peimisine (15 ÎŒ g/mL for 0–72 h) notably blocked the proliferation of human ovarian cancer cell through inducing apoptosis via increasing G0/G1 phase cell arrest [ 56 ].…”
Section: Pharmacologymentioning
confidence: 99%
“…Of course, some monomer chemical compositions have also been reported to exhibit advantageous effects on the treatment of endometrial cancer or ovarian cancer. A recent research suggested that peimisine (15 ÎŒ g/mL for 0–72 h) notably blocked the proliferation of human ovarian cancer cell through inducing apoptosis via increasing G0/G1 phase cell arrest [ 56 ].…”
Section: Pharmacologymentioning
confidence: 99%
“…This finding was consistent with that of Qi et al (2017) who proved the effect of verticine on cell viability, proliferation, and apoptosis of human leukemia and the function of reactive oxygen species and redox imbalance in this progress [ 10 , 11 ]. Some alkaloids could activate caspase-3 and caspase-dependent cell apoptosis [ 43 – 45 ], and stimulating the ROS production of K562 cell could promote caspase-3 expression and induce apoptosis [ 46 , 47 ]. Therefore, verticine might also activate caspase-3-related pathway in the process of stimulating ROS-induced apoptosis in K562/A02 cells.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…It is believed that alkaloids are the major biological active constituents (Li et al, 2013 ; Wang et al, 2014a ). Recent pharmacological studies found that alkaloids from BFC exhibit remarkable antitussive, expectorant, anti-inflammatory effects (Wang et al, 2011 , 2012 ), antiasthmatic effect (Yan, 2005 ), hypotensive property (Kang et al, 2004 ), anti-bacterial activity (Li et al, 2005 ), and antitumor effect (Wang D. D. et al, 2014 ; Wang et al, 2014b , 2015 ).…”
Section: Introductionmentioning
confidence: 99%